To Assess the Effectiveness of Planned Teaching on Knowledge Regarding Epilepsy in Children among the Anganwadi Workers (International Journal of Nursing Education, 2020)
Introduction: Epilepsy is a most common clinical entity in neurology clinics. The prevalence rates ofepilepsy in India are similar to those of developed country. However, the large treatment gap is a majorchallenge to our public health system. Perinatal injuries are a major causative factor in children. There arevery few epidemiological studies looking at the incidence of epilepsy from India. A state of Kerala withhigher literacy rates better the public health awareness (4.9/1000).1 a recent rural epilepsy surveillanceprogram from Uttarakhand showed a prevalence rate of two or more meaningless seizures to be 7.5 per1000.2A pediatric study from Kashmir valley shows prevalence rates of 3.74/1000 in males and 3.13/1000in females.3 A study conducted in Kolkata’s urban population showed an annual incidence rate of 27.27 per100,000 per year4 as per a recent study, 70 million people have epilepsy worldwide and nearly 90% of themare found in developing regions. [1] The study also estimated a median prevalence of 1.54% (0.48-4.96%)for rural and 1.03% (0.28-3.8%) for urban studies in developing countries.5Aims: The aim of the study is assess the effectiveness of planned teaching on knowledge regarding theepilepsy in children’s among the Anganwadi female workers in selected Anganwadi.Material and Method: The Descriptive evaluator approach was used in this study and the samplingtechnique was non probability convenient sampling was used. Data was collected using self structuredknowledge questionnaire and sample size was 110 Anganwadi female workers.Result: Study shows that pretest knowledge of anganwadi female worker3(2.73%)had poor level ofknowledge score,58(52.73%)had average level of knowledge,45(40.9%)had good knowledge and no onewas in excellent knowledge score, whereas in post test 65(59.09% had very good knowledge score and23(20.91%)had excellent knowledge score.Conclusion: Even though epilepsy is an eminently preventable and treatable condition, it still remains amajor public health problem due to high stigma, wide socioeconomic inequity, huge treatment gap and thepoor epilepsy healthcare delivery system in India. It is clearly evident that epilepsy is a complex publichealth problem that requires integrated multidisciplinary approach. Neurologists, public health professionals,psychiatrists, psychiatric social worker, psychiatric nurse and program managers need to join hands forprevention, improved care and rehabilitation of persons with epilepsy in India.